SHP-2-Mediated Upregulation of ZEB1 Is Important for PDGF-B-Induced Cell Proliferation and Metastatic Phenotype in Triple Negative Breast Cancer - Zhang, Lei; Yuan, Chenwei; Peng, Jing; Zhou, Liheng; Jiang, Yiwei; Lin, Yanping; Yin, Wenjin; Xu, Shuguang; Ma, Jun; Lu, Jinsong (Frontiers in Oncology, 2020)
Background: Triple negative breast cancer (TNBC), a fatal malignant tumor, is characterized by a lack of estrogen and progesterone hormone receptors and overexpression of HER2. Due to its characteristics, there are no effective targeted therapies for TNBC. Therefore, it is critical to identify the crucial factors that participate in modulating TNBC progression and explore the underlying molecular mechanism. Methods: CCK-8, bromodeoxyuridine incorporation, western blotting, qPCR, and transwell assays were utilized to evaluate breast cancer cell proliferation, migration, and invasion. Results: Activation of platelet-derived growth factor (PDGF)-B/PDGF receptor (PDGFR) promoted the proliferation and metastatic phenotype of TNBC cells; however, these effects were attenuated by SHP-2 knockdown. Moreover, PDGF-B promoted the expression of zinc finger E-box binding homeobox 1 (ZEB1) by downregulating the expression of miR-200. Furthermore, knockdown of ZEB1 mitigated the promoting effects of PDGF-B on cell proliferation and migration. In addition, the regulatory effects of PDGF-B on miR-200 and ZEB1 were mediated through the SHP-2/Akt pathway. Conclusion: Our findings highlight the important roles of PDGF-B/PDGFR and their downstream signaling pathways in regulating cell proliferation and metastatic phenotype in TNBC. Hence, these molecules may serve as novel therapeutic targets for TNBC in the future.